Transarterial chemoembolization in hepatocellular carcinoma with portal vein tumor thrombosis: a systematic review and meta-analysis. Issue 8 (August 2017) - Silva, Jack P.; Berger, Nicholas G.; Tsai, Susan; Christians, Kathleen K.; Clarke, Callisia N.; Mogal, Harveshp; White, Sarah; Rilling, William; Gamblin, T. Clark
Abstract: Background: Transarterial chemoembolization (TACE) for hepatocellular carcinoma (HCC) with portal vein thrombosis (PVT) remains controversial. This systematic review sought to examine the role of TACE in the treatment of HCC with PVT in either the main portal vein (MPV) or portal vein branches (PVB). Methods: PubMed was searched for "hepatocellular carcinoma" and "transarterial chemoembolization" from January 1, 2006 to August 31, 2016. Cohorts treated with TACE for HCC with PVT were included. Meta-analysis of overall survival (OS), mRECIST response, and complication incidence was performed. MPV and PVB subgroups were compared. Results: Of 136 search results, 13 studies with 1933 TACE patients were included. Median OS (95% CI) was eight (5–15) months. Survival rates after one, three, and five years were 29% (20%–40%), 4% (1%–11%), and 1% (0%–5%), respectively. Only 1% experienced liver failure and 18% had post-treatment complications. Patients with MPV thrombosis had worse survival than PVB patients (p < 0.001), but similar mRECIST response rates (14% vs. 16%, p = 0.238). Conclusion: TACE is a safe treatment for a highly selected population of HCC patients with PVT. Despite worse survival rates compared to PVB thrombosis, PVT in the MPV should not be considered an absolute contraindication to TACE.